An Artificial SEI Layer Based on an Inorganic Coordination Polymer with Self‐Healing Ability for Long‐Lived Rechargeable Lithium‐Metal Batteries. Issue 2 (16th December 2021) - Beichel, Witali; Skrotzki, Julian; Klose, Petra; Njel, Christian; Butschke, Burkhard; Burger, Stephan; Liu, Lili; Thomann, Ralf; Thomann, Yi; Biro, Daniel; Thiele, Simon; Krossing, Ingo
Abstract: Upon immersion of a lithium (Li) anode into a diluted 0.05 to 0.20 M dimethoxyethane‐solution of the phosphoric acid derivative (CF3 CH2 O)2 P(O)OH (HBFEP), an artificial solid electrolyte interphase (SEI) is generated on the Li‐metal surface. Hence, HBFEP reacts on the surface to the corresponding Li salt (LiBFEP), which is a Li‐ion conducting inorganic coordination polymer. This film exhibits – due to the reversibly breaking ionic bonds – self‐healing ability upon cycling‐induced volume expansion of Li. The presence of LiBFEP as the major component in the artificial SEI is proven by ATR‐IR and XPS measurements. SEM characterization of HBFEP‐treated Li samples reveals porous layers on top of the Li surface with at least 3 μm thickness. Li−Li symmetrical cells with HBFEP‐modified Li electrodes show a three‐ to almost fourfold cycle‐lifetime increase at 0.1 mA cm −2 in a demanding model electrolyte that facilitates fast battery failure (1 M LiOTf in TEGDME). Hence, the LiBFEP‐enriched layer apparently acts as a Li‐ion conducting protection barrier between Li and the electrolyte, enhancing the rechargeability of Li electrodes. Abstract : Self‐healing SEI layer : The deposition of a fluoro‐organic phosphoric acid on Li metal results in the formation of an artificial SEI layer on its surface. This layer enables a substantial cycle lifetime enhancement in Li−Li symmetrical cells. The main constituent of the formed layer is a Li‐ion conducting coordination polymer with adaptive self‐healing ability.